Standards of diagnostic colonoscopy for early‐stage neoplasia: Recommendations by an Asian private group - Sano, Yasushi; Chiu, Han‐Mo; Li, Xiao‐bo; Khomvilai, Supakij; Pisespongsa, Pises; Co, Jonard Tan; Kawamura, Takuji; Kobayashi, Nozomu; Tanaka, Shinji; Hewett, David G.; Takeuchi, Yoji; Imai, Kenichiro; et al. (Wiley, 2019)
Background and Aim: In recent years, the incidence of colorectal cancer has been increasing, and it is now becoming the major cause of cancer death in Asian countries. The aim of the present study was to develop Asian expert-based consensus to standardize the preparation, detection and characterization for the diagnosis of early-stage colorectal neoplasia. Methods: A professional group was formed by 36 experts of the Asian Novel Bio-Imaging and Intervention Group (ANBI2G) members. Representatives from 12 Asia–Pacific countries participated in the meeting. The group organized three consensus meetings focusing on diagnostic endoscopy for gastrointestinal neoplasia. The Delphi method was used to develop the consensus statements. Results: Through the three consensus meetings with debating, reviewing the literature and regional data, a consensus was reached at third meeting in 2016. The consensus was reached on a total of 10 statements. Summary of statements is as follows: (i) Adequate bowel preparation for high-quality colonoscopy; (ii) Antispasmodic agents for lesion detection; (iii) Image-enhanced endoscopy (IEE) for polyp detection; (iv) Adenoma detection rate for quality indicators; (v) Good documentation of colonoscopy findings; (vi) Complication rates; (vii) Cecal intubation rate; (viii) Cap-assisted colonoscopy (CAC) for polyp detection; (ix) Macroscopic classification using indigocarmine spray for characterization of colorectal lesions; and (x) IEE and/or magnifying endoscopy for prediction of histology. Conclusion: This consensus provides guidance for carrying out endoscopic diagnosis and characterization for early-stage colorectal neoplasia based on the evidence. This will enhance the quality of endoscopic diagnosis and improve detection of early-stage colorectal neoplasia. © 2018 The Authors. Digestive Endoscopy published by John Wiley & Sons Australia, Ltd on behalf of Japan Gastroenterological Endoscopy Society.